Efeito do estresse mineral induzido por fontes e doses de potássio na produção de raízes em plantas de berinjela (Solanum melongena L.) - Marques, Douglas Jose [UNESP]; Broetto, Fernando [UNESP]; da Silva, Ernani Clarete (Univ Fed Rural Semi-arido-ufersa, 2010)
This study was carried out at the Department of Plant Production, Sector Horticulture, São Paulo State University-UNESP, Botucatu Campus, São Paulo State, Brazil in order to evaluate the effect of sources and increasing doses of potassium in roots of eggplant. The experimental design was randomized blocks in factorial scheme 2 x 4 (two sources of potassium: KCl and K(2)SO(4) and four doses of K(2)O, 250, 500, 750 and 1000 kg ha(-1)) and three replications. For the experiment, we used Oxisol medium texture (615 g of sand, 45 g of silt and 340 g of clay per kg soil). The soil passed through sieve of 5 mm and packed in plastic pots with a capacity of 32 liters of soil where plants were grown. The pots were distributed with a spacing of 0,63 m between plants and 1,0 m between rows each pot being grown with a plant. The evaluated characteristics were: root dry mass and volume of the root. It was concluded that sources and excessive doses of mineral K(2)O induces stress in eggplants and affect the roots being less harmful K(2)SO(4) source.

O presente trabalho foi conduzido no Departamento de Produção Vegetal, setor de Horticultura, da UNESP - Campus de Botucatu, SP com o objetivo de avaliar o efeito de fontes e doses crescentes de potássio em raízes de berinjela. O experimento foi disposto em delineamento de blocos casualizados, em esquema fatorial 2 x 4 (duas fontes de potássio: KCl e K2SO4 e quatro doses de K2O, 250, 500, 750 e 1000 kg ha-1) e três repetições. Para a condução do experimento, utilizou-se Latossolo Vermelho distroférrico de textura média (615 g de areia, 45 g de silte e 340 g de argila por quilograma de solo). O solo passou em peneira de 5 mm sendo acondicionado em vasos plásticos com capacidade para 32 L de solo onde as plantas foram cultivadas. Os vasos foram distribuídos com espaçamento de 0,63 m entre plantas e 1,0 m entre linhas sendo cada vaso cultivado com uma planta. As características avaliadas foram: massa seca da raiz e volume da raiz. Conclui-se que fontes e doses excessivas de K2O induziram ao estresse mineral em plantas de berinjela e afetaram as raízes, sendo menos prejudicial o K2SO4.
Effect of mineral stress-induced sources and doses of potassium on the production of root in eggplants (Solanum melongena L.)
Keywords: Solanum melongena L; Potassium; Root; Dry matter